2019
DOI: 10.3899/jrheum.180775
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Antibiotic-refractory Lyme Arthritis: A Multicenter Case-control Study

Abstract: Objective.Few factors have consistently been linked to antibiotic-refractory Lyme arthritis (ARLA). We sought to identify clinical and treatment factors associated with pediatric ARLA.Methods.We performed a case-control study in 3 pediatric rheumatology clinics in a Lyme-endemic region (2000–2013). Eligible children were aged ≤ 18 years with arthritis and had positive testing for Lyme disease by Western blot. Cases were 49 children with persistently active arthritis despite ≥ 8 weeks of oral antibiotics or ≥ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
9
0
7
Order By: Relevance
“…Bislang lassen sich nur wenige demografische, klinische oder laborchemische Prädiktoren für den Verlauf einer Lyme-Arthritis definieren. So befanden sich neben älteren Kindern und Jugendlichen in einzelnen Kohorten auch vermehrt weibliche Patienten unter den Patienten mit protrahiertem Verlauf nach antibiotischer Therapie 20 , 24 . Zudem sind die Patienten mit „Antibiotika-refraktärem“ Verlauf eher durch eine Monoarthritis charakterisiert, wohingegen eine oligoartikuläre Manifestation sowie eine ausgeprägte systemische Entzündungsreaktion zu Beginn der Arthritis eher positive Prädiktoren für ein primäres Ansprechen auf die antibiotische Therapie sind 20 .…”
Section: Postinfektiöse („Antibotika-refraktäre“) Lyme-arthritisunclassified
See 3 more Smart Citations
“…Bislang lassen sich nur wenige demografische, klinische oder laborchemische Prädiktoren für den Verlauf einer Lyme-Arthritis definieren. So befanden sich neben älteren Kindern und Jugendlichen in einzelnen Kohorten auch vermehrt weibliche Patienten unter den Patienten mit protrahiertem Verlauf nach antibiotischer Therapie 20 , 24 . Zudem sind die Patienten mit „Antibiotika-refraktärem“ Verlauf eher durch eine Monoarthritis charakterisiert, wohingegen eine oligoartikuläre Manifestation sowie eine ausgeprägte systemische Entzündungsreaktion zu Beginn der Arthritis eher positive Prädiktoren für ein primäres Ansprechen auf die antibiotische Therapie sind 20 .…”
Section: Postinfektiöse („Antibotika-refraktäre“) Lyme-arthritisunclassified
“…Dennoch unterscheidet sich das klinische Bild und der Verlauf unter entzündungshemmender Therapie zu dem anderer entzündlich-rheumatischer Gelenkerkrankungen (rheumatoide Arthritis, juvenile Idiopathische Arthritis, Spondylarthropathien). Die postinfektiöse Lyme-Arthritis tritt in jedem Lebensalter auf [20,[24][25][26][27][28][29]. In einzelnen pädiatrischen Kohorten zeigte sich jedoch ein vermehrtes Auftreten mit steigendem Lebensalter [20,24].…”
Section: Klinisches Bildunclassified
See 2 more Smart Citations
“…Thus, the SERA IgG and IgM Lyme assays may significantly increase case detection while reducing false positive rates.Available diagnostic tests for Lyme disease (STTT and MTTT) do not readily distinguish between the three stages, which include i) early localized disease, ii) early disseminated disease, and iii) late Lyme disease(35). Yet, knowledge of disease stage can be important to guide appropriate dose and duration of antibiotic therapy(36). Others have suggested that the number of positive immunoblot bands or epitopes is a useful metric to stage disease(14, 37).In accordance with this hypothesis, we observed a statistically significant increase in the number of positive motifs in cases of Lyme arthritis.…”
mentioning
confidence: 99%